EFEITOS DA INCORPORAÃ‡ÃƒO DE â€œCAPIM CARRAPICHOâ€ ð˜Šð˜¦ð˜¯ð˜¤ð˜©ð˜³ð˜¶ð˜´ ð˜¦ð˜¤ð˜©ð˜ªð˜¯ð˜¢ð˜µð˜¶ð˜´ (L.), SOBRE O pH, H+, Al3+ E CAPACIDADE DE RETENÃ‡ÃƒO DE UMIDADE DE SOLOS DO MUNICÃPIO DE PIRACICABA - Mello, Francisco de A. F. de; Freire, Francisco M.; Casagrande, JosÃ© Carlos; Chitolina, JosÃ© Carlos; Pedras, JosÃ© Figueiredo; Stolf, Rubismar (REVISTA DE AGRICULTURA, 2020)
EFEITOS DA INCORPORAÃ‡ÃƒO DE â€œCAPIM CARRAPICHOâ€ ð˜Šð˜¦ð˜¯ð˜¤ð˜©ð˜³ð˜¶ð˜´ ð˜¦ð˜¤ð˜©ð˜ªð˜¯ð˜¢ð˜µð˜¶ð˜´ (L.), SOBRE O pH, H+, Al3+ E CAPACIDADE DE RETENÃ‡ÃƒO DE UMIDADE DE SOLOS DO MUNICÃPIO DE PIRACICABA